2019
DOI: 10.14260/jemds/2019/638
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Day Time Sleepiness and Academic Performance in First Year Medical Students

Abstract: BACKGROUND Sleep deprivation would result in sleepiness during learning activities, with impairment of cognitive abilities and psychological wellbeing. Medical training, with its immense workload in a highly stressful environment, makes students especially vulnerable to poor sleep. This study evaluated the impact of sleep quality and related factors on academic performance in medical students of first academic year. METHODS This is a cross sectional study. 138 students in the first academic year of MBBS course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In the present study a significant association was not observed between sleep quality assessed by PSQI and academic performance. Our result was in line with the study conducted among first year medical students in Kerala 16 Moreover academic performance of students also depends upon their commitment, concentration, motivation towards academic activities. Along with sleep disturbances, incidence of burnout is found to be reported higher among business students, medical students and dental students.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study a significant association was not observed between sleep quality assessed by PSQI and academic performance. Our result was in line with the study conducted among first year medical students in Kerala 16 Moreover academic performance of students also depends upon their commitment, concentration, motivation towards academic activities. Along with sleep disturbances, incidence of burnout is found to be reported higher among business students, medical students and dental students.…”
Section: Discussionsupporting
confidence: 91%
“…On an average we spend about 30% of our lives asleep (Foster, 2012). Sleep is an active, repetitive and reversible behavior serving several different functions, such as repair and growth, learning or memory consolidation, and restorative processes (Thomas and Sundar, 2019). Good sleep is advantageous to improve the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The quality and quantity of sleep could be detrimental to the person's quality of life and ability to function, especially for those practicing high physically and mentally demanding professions such as dentistry (Elagra et al, 2016). Sleep deprivation would result in sleepiness during learning activities, with impairment of cognitive abilities and psychological well being (Thomas and Sundar, 2019). It is important to stress that sleep disruption is much more than an individual's frustration at failing to initiate and sustain sleep, or even the sensation of feeling sleepy at an inappropriate time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The academic performances of different years of students vary as their ability to adapt to their study hours and accurate management of stress establishes. 11 Excessive daytime sleepiness (EDS) is common among university students and has many adverse consequences, out of which academic performance is the one that is affected the most. 12 There are certain factors important to score high grades in exams i.e., declarative knowledge, procedural knowledge, cognitive processing and memory.…”
Section: Introductionmentioning
confidence: 99%